Plan de capacitacion para la empresa alumcol de la provincia de santo domingo de tsachilas - Intriago Loor, Gardenia Monserrate (2011)
Alumcol company private ono it was founded in 1995 by initiative of its owner, Mr Sandro Eduardo Intriago, which aims to promote comprehensive and harmonious development from previous years had identified the need for a service in aluminum and glass that would complement the growth in housing construction in the province and its surroundings Tsachila. This research is aimed at the company Alumcol company is located in the Province of Santo Domingo de los Tsáchilas Avenue in Santa Rosa and Pedro Vicente Maldonado. It has as aims to present the results and conclusions obtained by the investigator of a comprehensive study that will allow a better strategy for the company's progress. One of the main problems facing the company today is not knowing exactly the potential of its employees as in the production area there is no liability to the development of the works in time so is a delay and economic loss for the company, in the administrative area there is no control for the production area for which the company does not produce enough to satisfy the customer, lack of training did not allow optimal care in care customer In this research we used field research, literature or documentary follows likewise apply inductive and deductive, analytic-synthetic. Techniques and assessment tools were applied to survey employees, customers, assets, liabilities customers of the company after the interviews were applied to the top as the General Manager and Manager of the company Alumcol. In the results of surveys of active clients Alumcol company gives us the conclusion that it must improve relations between empledos and customers as it is regular percentage. The workforce that the company offers is acceptable Alumcol active customers as customers think otherwise passive. In surveys of employees of the company gives us the result that no employee was trained in the work area at the time of entry to work at the company for what they consider necessary for the company to provide training to all staff. In the settlement proposal was elaborated a training plan for the administrative and production staff